Juridical study of the criminal act of defamation article 310 paragraph (1) of the Indonesian criminal law code (KUHP) - Muhamad yanto (Journal of Law Science, 2023)
The object of research as well as a problem in this research is the provision of criminal acts under Indonesian positive criminal law (KUHP), as well as the basis for judges deciding probation sentences against perpetrators of criminal offenses of Article 310 paragraph (1) of the Criminal Code.. Acts that offend honor in this sexual field do not include crime, decency or morality crimes referred to in Article 281 to Article 303 of the Criminal Code. The provisions of the defamation are stipulated in Chapter XVI concerning Insults, Book I specifically Articles 310, 311, 315, 317 and Article 318 of the Criminal Code. In addition to those stipulated in the Criminal Code, matters relating to "Defamation" are also regulated in Law Number 11 of 2008 concerning information and electronic transactions. therefore, on the basis of judicial legal considerations with this conditional criminal verdict, I am not in agreement because the defendant has been proven to violate the principle of legality and there is an element of error, defaming the victim witness. In addition, in my view, the Criminal Code is more likely to protect the rights of defendants than a sense of justice for victims of criminal acts. In examining and adjudicating cases of defamation (blasphemous crimes), the judge needs to consider the situation of the victim witness, with the aim of protecting the dignity and honor of the victim, so that the verdicts are met with a sense of justice. Although, giving a verdict is the authority of a judge, it must also consider the prosecutor's demands, also consider the main elements in the teachings of criminal liability,